Physiological and biochemical responses of Kinnow mandarin (Citrus nobilis × Citrus deliciosa) to EMS induced mutagenesis - KUMAR, SUNIL; AWASTHI, O P; SHARMA, R M; PRADHAN, SATYABRATA (The Indian Journal of Agricultural Sciences, 2021)
The present study was carried out to enhance the genetic variability in Kinnow mandarin (Citrus nobilis Loureiro Physiological and biochemical responses of Kinnow mandarin (Citrus nobilis × Citrus deliciosa) to EMS induced mutagenesis Citrus deliciosa Tenora) using ethyl methanesulfonate (EMS) during 2016-17 and 2017-18. Plants created with different doses of EMS concentration, viz. 0.05%, 0.1%, 0.2% and 0.5% were examined for the various physiological and biochemical alterations in putative mutants aged six years and compared with the wild type (WT). A dose-dependent decrease in leaf area was recorded in the mutants with increasing doses of EMS concentration and as compared to WT, maximum reduction of 135.52 and 104.92% was witnessed in the mutants E-19 and E-17 developed from 0.5% EMS, whereas the leaves were more succulent in E-16. Chlorophyll a content was higher than chlorophyll b in the mutated population. As compared to WT, maximum decrease in chlorophyll a, total chlorophyll was noticed in the mutants E-19 generated from 0.5% EMS. Contrary to the physiological alterations, the total phenol, proline and total protein content in the mutants were upregulated by nearly two fold in the mutants developed beyond 0.1% EMS. Significant increase was also noticed in the antioxidant enzymes SOD, CAT, POX and GR activity in the mutants E-16 to E-20 induced from 0.5% EMS. The variation in traits of interest observed in the present study such as better leaf succulency and upregulated antioxidant enzyme activity in the mutant E-16 (0.5% EMS) suggests that the developed mutant could be utilised in Kinnow improvement for abiotic stress tolerance.